Les sables de Fontainebleau: a natural quartz reference sample and its characterisation - Kreutzer, Sebastian; Friedrich, Johannes; Sanderson, David; Adamiec, Grzegorz; Chruścínska, Alicja; Fasoli, Mauro; Martini, Marco; Polymeris, George S.; Burbidge, Christopher I.; Schmidt, Christoph (Ancient TL, 2017)
Fundamental studies on luminescence production in natural quartz require samples which can be studied by groups of laboratories using complementary methods. In the framework of a European collaboration studying quartz luminescence, a sample originating from the Fontainebleau Sandstone Formation in France was selected for characterisation and distribution to establish a starting point for interlaboratory work. Here we report on the preparation and characterisation work undertaken before distribution with the aim of ensuring that each laboratory received comparable material. Material was purified to enrich the quartz concentration, followed by mineralogical screening by SEM and ICP-MS analyses. Luminescence screening measurements were undertaken at a single laboratory (SUERC) to verify the suitability of the sample for use within the study, and to establish the level of homogeneity of subsamples prepared for distribution. The sample underwent minimal non-chemical pre-treatment by multiple cycles of magnetic separation and annealing. SEM analysis showed that the sample consists mainly of SiO2. The luminescence characterisation confirmed a dose sensitivity of ca. 22,000-160,000 cts K−1 Gy−1 per 260-290 grains for the 110◦C UV TL peak, well developed low (here: 100-300◦C) temperature (pre-dose) TL signals and high OSL sensitivities. The grain to grain OSL response varies by more than one order of magnitude. No significant IRSL signal was observed. In summary, the results from luminescence characterisation confirm the suitability of the sample for the luminescence experiments envisaged and have established a basis for comparability in studies conducted by a network of laboratories.
Gesehen am 27.03.2025